PERAN CONSCIENTIOUSNESS TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA MAHASISWA - Keyra Aurielle Shevanka; Nirmala Putri Ramadhani; Aldzikra Dhaifa Syavanay Miraza; Naurah Fairuz Zakiyah; Annisa Risma Devita Suhendar Pudiwan; Najwa Zhafira Khairunnisa; Sri Maslihah (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Students are in the emerging adulthood phase, which is characterized by increasing academic, social, and personal demands, requiring adequate self-regulation to maintain psychological well-being. This study aims to examine the relationship between conscientiousness and psychological well-being among students. A quantitative approach with a correlational design was employed. The participants consisted of 309 students from various universities in Indonesia. Data were analyzed using Spearman’s correlation test. The results revealed a significant positive relationship between conscientiousness and psychological well-being with a moderate correlation strength [r(307) = 0.418; p < 0.001]. This finding indicates that higher levels of conscientiousness are associated with higher psychological well-being. Traits such as discipline, responsibility, orderliness, and goal orientation contribute to better management of academic demands, reduced psychological distress, and enhanced feelings of competence and meaning. Conversely, lower conscientiousness may increase the risk of psychological distress due to poor time management and self-control. Most participants were categorized at a moderate level, indicating adequate adaptive capacity with room for further improvement. ABSTRAKMahasiswa berada pada fase emerging adulthood yang ditandai dengan meningkatnya tuntutan akademik, sosial, dan personal, sehingga memerlukan kemampuan regulasi diri yang baik untuk menjaga kesejahteraan psikologis. Penelitian ini bertujuan untuk menguji hubungan antara conscientiousness dan kesejahteraan psikologis pada mahasiswa. Pendekatan yang digunakan adalah kuantitatif dengan desain korelasional. Subjek penelitian berjumlah 309 mahasiswa yang berasal dari berbagai perguruan tinggi di Indonesia. Analisis data menggunakan uji korelasi Spearman. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara conscientiousness dan kesejahteraan psikologis dengan kekuatan hubungan sedang [r(307) = 0,418; p < 0,001]. Temuan ini mengindikasikan bahwa semakin tinggi tingkat conscientiousness, semakin tinggi pula kesejahteraan psikologis mahasiswa. Karakteristik seperti disiplin diri, tanggung jawab, keteraturan, dan orientasi tujuan berperan dalam membantu individu mengelola tuntutan akademik, mengurangi tekanan psikologis, serta meningkatkan perasaan kompeten dan bermakna. Sebaliknya, tingkat conscientiousness yang rendah berpotensi meningkatkan risiko tekanan psikologis akibat lemahnya pengelolaan waktu dan kontrol diri. Mayoritas responden berada pada kategori sedang, yang menunjukkan kapasitas adaptif yang cukup baik namun masih dapat dioptimalkan.